Development оf Model оf System оf Regional Institutes оf Development in the Conditions of Formation of Innovative Knowledge-Intensive Economy - V. V. Bondarenko (Мир новой экономики, 2018)
Results of the analysis of dependence of level of socio-economic indexes of the region (VRP, average per capita monetary income of the population, income of the consolidated budget of the territorial subject of the federation and number of the personnel occupied with research and development) from the level of profitability of activity of regional institutes of development are presented in article. The system of regional institutes of development representing set of the interconnected elements is developed: factors of the external environment, subject, object and methods of management. Realization of this system will allow to raise indicators of efficiency of regional institutes of development and to reach positive social and economic effects at the level of the region. Realization of the developed system of regional institutes of development will promote increase in level of regional development of subjects of the Russian Federation, will allow to develop the most perspective grow also the directions of regional economy.